EMPATI DAN PERILAKU MEROKOK DI TEMPAT UMUM - Ari Tris Ochtia Sari; Neila Ramdhani; Mira Eliza (Jurnal Psikologi, 2003)
Do the emphaty determine the smoking behavior? And is the smoking behavior in the public areas, such as in the train station, in the cinema, in the cafetaria, in the car park, and on the bus affected by the low of empathy.? One hundred and fifty students, 15-22 years old participated in this study. They were asked to fill the Emphaty Scales (SE) and Smoking Behavior Scales (SPM) in when they were smoking in the public area. The Product Moment analysis showed that there is a negative correlation (-0,207) between the two. The higher the emphatetic the lower the smoking behavior, especially in the public areas. This research also found out that the frequency of smoking is related to the empathy. Therefore, people who smoke in the public areas should be the hard smokers. Keywords: Emphaty, Smoking Behavior, Public Area.